Twenty thousand leagues under the sea - Verne, Jules, 1828-1905 (Classics illustrated (Newbury (England)), 2016)
Presents a graphic adaptation of Jules Verne's story about the adventures of a French professor and his two companions as they sail above and below the world's oceans as prisoners on the fabulous electric submarine of the deranged Captain Nemo. Includes a biography of Verne, theme discussions, and study questions.